Equity in Higher Education – Portuguese Perspective - Jesuino, Jorge (2017)
Access, participation and exclusion from higher education for marginalized and disadvan-taged sections of the population are an intricate socio-political as well as economic practice that has manifold explanations and outcomes. During the last three decades, the higher education has experienced expansion in both enrolments and institutions. The approaches and means of delivery have changed besides the diversification in provision. The role of the state and mar¬ket has also reformed. This characteristic has also altered the nature of equity in higher edu¬cation across the globe. The chapters of this book on different countries of Asia, Europe and Latin America examine access and describe the several spaces where cohorts of relevant age group are included, excluded, or are at threat of exclusion in higher education. The chapters also narrate the state of affairs in which despite numerous alike structure in the experience and outcomes of social exclusion across disenfranchised groups and regions, how some critical differences have led to different paths of struggles and policy formation to attain the objective of equity in higher education.